Levels of Disclosure in Financial Reports According to the Financial Literacy of Their Users and the Mechanism for Determining Them by Artificial Intelligence Techniques - Muhammad Ali Jaafar (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The research aimed to analyze the relationship between the financial literacy of financial report users and the required level of disclosure, and to propose an intelligent mechanism based on artificial intelligence techniques to customize report content. The research variables were identified as: financial literacy (high, medium, low) and disclosure level (basic, medium, advanced), with a study of the effects of age and educational level. The research adopted a mixed methodology (descriptive and analytical) using machine learning models (Random Forest) and analysis of a questionnaire consisting of 15 questions. The research sample included 150 participants from Baghdad Bank and Asia Islamic Bank of Iraq, with 155 questionnaires distributed (electronically and on paper), excluding 5 incomplete questionnaires. The results showed a strong positive correlation between financial literacy and the level of disclosure, where 75% of those with high financial literacy preferred advanced reports. The artificial intelligence model also recorded an accuracy of 82% in predicting the optimal level of disclosure. The research recommended adopting intelligent customizable financial reports through artificial intelligence and enhancing users' financial literacy to improve decision quality.